WAWASAN AL-QURAN DAN SUNNAH TENTANG PARIWISATA - Johar Arifin (Jurnal An-Nur, 2015)
Tourism world today is very sad as a result of their impact , such as promiscuity , alcoholism , drug trafficking, and so forth . Observer tourism continues to make a breakthrough so that the development of tourism can be a positive impact on people's lives . This paper provides an overview of the Quran and the Sunnah of tourism , both associated with the recommendation , purpose , ethics , basic prinsif Islam and Islamic tourism management so that the future of world tourism becomes part of the mental and spiritual development of society .This paper is also expected to contribute positively to the Government in this case the Department of Tourism and Culture at both district / municipal , provincial and national basis in order to develop tourism in the future .